Ответ:
см ниже
Пошаговое объяснение:
[tex]\frac{2}{3}[/tex] x - [tex]\frac{1}{18}[/tex] x + [tex]\frac{1}{2}[/tex] =2 [tex]\frac{2}{9}[/tex]
х*( [tex]\frac{2}{3}[/tex] - [tex]\frac{1}{18}[/tex] ) =2 [tex]\frac{2}{9}[/tex] - [tex]\frac{1}{2}[/tex]
х* [tex]\frac{2*6-1}{18}[/tex] =2 + [tex]\frac{2*2-9}{18}[/tex]
[tex]\frac{11}{18}[/tex] х= 2 + (- [tex]\frac{5}{18}[/tex])
[tex]\frac{11}{18}[/tex] х= 1 + [tex]\frac{18-5}{18}[/tex]
[tex]\frac{11}{18}[/tex] х= 1 [tex]\frac{13}{18}[/tex]
[tex]\frac{11}{18}[/tex] х= [tex]\frac{31}{18}[/tex]
х= [tex]\frac{31}{18}[/tex] : [tex]\frac{11}{18}[/tex] используя свойства деления дробей
х= [tex]\frac{31}{18}[/tex] * [tex]\frac{18}{11}[/tex]
х= [tex]\frac{31}{11}[/tex]
х= 2 [tex]\frac{9}{11}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
см ниже
Пошаговое объяснение:
[tex]\frac{2}{3}[/tex] x - [tex]\frac{1}{18}[/tex] x + [tex]\frac{1}{2}[/tex] =2 [tex]\frac{2}{9}[/tex]
х*( [tex]\frac{2}{3}[/tex] - [tex]\frac{1}{18}[/tex] ) =2 [tex]\frac{2}{9}[/tex] - [tex]\frac{1}{2}[/tex]
х* [tex]\frac{2*6-1}{18}[/tex] =2 + [tex]\frac{2*2-9}{18}[/tex]
[tex]\frac{11}{18}[/tex] х= 2 + (- [tex]\frac{5}{18}[/tex])
[tex]\frac{11}{18}[/tex] х= 1 + [tex]\frac{18-5}{18}[/tex]
[tex]\frac{11}{18}[/tex] х= 1 [tex]\frac{13}{18}[/tex]
[tex]\frac{11}{18}[/tex] х= [tex]\frac{31}{18}[/tex]
х= [tex]\frac{31}{18}[/tex] : [tex]\frac{11}{18}[/tex] используя свойства деления дробей
х= [tex]\frac{31}{18}[/tex] * [tex]\frac{18}{11}[/tex]
х= [tex]\frac{31}{11}[/tex]
х= 2 [tex]\frac{9}{11}[/tex]